The Comparison of Medical Students Attitudes and Performance Regarding Different Types of Academic Cheating During Clinical Courses - Mitra Amini; Marjan Parizad; Sara Rivaz; Mohammad Mehdi Sagheb; Mozhdeh Rivaz (Kerman University of Medical Sciences, 2016)
Background & Objective: Cheating in the university can be a predictor of workplace fraud and workplace fraud among physicians and specialists will have negative consequences This study was performed for the purpose of determining the prevalence of all kinds of cheating among medical students which were in their last three years of Medical School at Shiraz University of Medical Sciences Iran in 2010 Methods: The study sample consisted of 136 medical students in their last three years of study The participants were selected through simple random sampling The data collection tool was a selfadministered questionnaire The validity of the questionnaire was confirmed by experts and its reliability was reported as 087 in a study Data were analyzed using descriptive statistics and independent ttest (for the variable of gender) in SPSS statistical software Results: All students answered the questionnaire; thus the response rate was 100% Among the respondents 64% were male and the rest female According to the results more than 80% of students had experienced copying during an exam at least once during the academic period Moreover 25% of students have performed at least one kind of plagiarism in writing their thesis and essays The performance of medical students in the clinical course showed that 50% of students had cheated at least once during their academic period The rate of cheating was significantly lower in female students Conclusion: Although the majority of students have a positive attitude and believe cheating to be a dishonest action half of them have cheated This may be due to stress caused by examinations Therefore it seems that students behaviors should be changed and they must receive the necessary training in this regard so that stress is not the cause of fraud and this phenomenon is inhibited